Testbed or Thoroughfare? Africa's Place in China's Evolving Grand Strategy - Carmody, Padraig (My University, 2026)
What is Africa’s place in China’s global geo-strategy, or does it have one? China’s engagements with the continent have increased markedly in recent decades but does it occupy a central or peripheral role in China’s grand strategy? Recently, there have been debates about whether China has such a strategy, but we argue that part of the confusion around these issues arises from the distinctive nature of that state and the forms of loose coordination it operationalizes. Rather than a strictly defined ‘grand strategy’, China has a grand, strategic-relational approach to its foreign policy or operates a relational geopolitical code which nonetheless reflects core interests. We bring this perspective to bear on Africa’s evolving positionality in China’s global geostrategic engagements in order to evaluate its significance.
ACCEPTED
Keywords: China; Africa; grand strategy; geopolitics; state power; relationality; China, Africa, grand strategy; International Development